AKTIVITAS FISIK LANSIA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS GIMPU KECAMATAN KULAWI SELATAN KABUPATEN S - Indah Sari, Andi Nur; Jumain; Alta Lariksah (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Physical deterioration in the elderly will cause changes in vital organs which include changes in the cardiovascular system and elimination systems such as the kidneys. Changes in body organs will cause various diseases such as hypertension. Risk factors for hypertension are divided into two, namely factors that can be changed and cannot be changed. One factor that can be changed is physical activity. Hypertension is one of the diseases that is included in the category of the 5 biggest diseases at the Gimpu Health Center. The aim of this research was to determine the physical activity of elderly people with hypertension in the work area of the Gimpu Health Center, South Kulawi District, Sigi Regency. This type of research is descriptive research. The data used is primary and secondary data. Data analysis using univariate analysis. The population in this study was 194 with a total of 66. The sampling technique was proportional random sampling. The research results showed that 29 or 43.9% of respondents had light physical activity, 23 or 34.8% of respondents had moderate physical activity and 14 or 21.2% of respondents had heavy physical activity. In conclusion, the physical activity of elderly people with hypertension in the Gimpu Health Center Working Area is light physical activity. It is recommended that the Gimpu Health Center pay more attention to the level of hypertension in the elderly in the work area in the future and become a protector in maintaining public health and become an agency that can serve the community in terms of improving the health status of the elderly.